2021
DOI: 10.1371/journal.pone.0246307
|View full text |Cite
|
Sign up to set email alerts
|

Leptin improves the in vitro development of preimplantation rabbit embryos under oxidative stress of cryopreservation

Abstract: Vitrification is an economically effective method for embryo cryopreservation in human and livestock animals; however, it carries the risk of damage by the exposure to severe oxidative stress. The present study was conducted to evaluate the effect of leptin at different levels on the in vitro development of fresh and vitrified preimplantation embryos in a rabbit model. Normal embryos at morulae stage were randomly cultured for 2 h with 0, 10, 20 or 100 ng/mL of leptin, then were cultured for further 48 h as fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…In another in vitro study, it was noted that leptin significantly decreased pro-oxidant biomarkers such as MDA and NO and increased antioxidant markers such as total antioxidant capacity (TAC), SOD, and GPx against cryopreservation-induced oxidative stress in rabbit embryos. It has been suggested that leptin can be used as an antiapoptotic and antioxidant promoter to support embryonic development in vitro under oxidative stress induced by cryopreservation [114]. In one study, treatment with high glucose caused an increase in oxidative stress in pheochromocytoma (PC12) cells with excessive ROS and MDA production and depletion of GSH content, however, leptin treatment caused a decrease in MDA and ROS levels and an increase in GSH content, resulting in hyperglycemic PC12 cells.…”
Section: Leptin Signaling Pathways Pomc;pro-opiomelanocortin Socs3; Intracellular Suppressor Of Cytokine Signal 3 Ptp1b; Protein Tyrosinementioning
confidence: 99%
“…In another in vitro study, it was noted that leptin significantly decreased pro-oxidant biomarkers such as MDA and NO and increased antioxidant markers such as total antioxidant capacity (TAC), SOD, and GPx against cryopreservation-induced oxidative stress in rabbit embryos. It has been suggested that leptin can be used as an antiapoptotic and antioxidant promoter to support embryonic development in vitro under oxidative stress induced by cryopreservation [114]. In one study, treatment with high glucose caused an increase in oxidative stress in pheochromocytoma (PC12) cells with excessive ROS and MDA production and depletion of GSH content, however, leptin treatment caused a decrease in MDA and ROS levels and an increase in GSH content, resulting in hyperglycemic PC12 cells.…”
Section: Leptin Signaling Pathways Pomc;pro-opiomelanocortin Socs3; Intracellular Suppressor Of Cytokine Signal 3 Ptp1b; Protein Tyrosinementioning
confidence: 99%